Wujud Implementasi Pendidikan yang Memerdekakan Peserta Didik di Indonesia - Layla, Jaova (Lembaga Yasin AlSys, 2024)
Education is a conscious effort made by humans to develop and shape humans according to their potential in order to improve the quality of their lives. Liberating education is education that gives students the freedom to grow and develop according to their nature. The implementation of education that liberates students is realized by Ki Hajar Dewantara in implementing the among system at Perguruan Taman Siswa. The among system implemented by Ki Hajar Dewantara is based on the principles of independence and humanity. The implementation of liberating education is also used by the Minister of Education in running the current education system. The form of implementation is in the form of an independent learning curriculum. Merdeka Belajar implement the student-centered education. Students are given the freedom to determine their learning goals. The curriculum of Merdeka Belajar creates learning practices that enable teachers and students to innovate and be creative freely according to their needs, so that students can learn according to their nature.